A review of the evolution, biostratigraphy, provincialism and diversity of Middle and early Late Triassic conodonts. (1st December 2015) - Chen, Yanlong; Krystyn, Leopold; Orchard, Michael J.; Lai, Xu‐Long; Richoz, Sylvain
Abstract: The taxonomy, diversity, evolutionary lineages, and stratigraphical distributions of Middle and early Late Triassic conodonts are reviewed and re‐evaluated. Twenty‐five genera are recognized in the Middle and early Late Triassic, including a new genus cited in open nomenclature. Of these, 24 genera are assigned to two families and seven subfamilies. The family Gondolellidae consists of the subfamilies Cornudininae, Epigondolellinae, Neogondolellinae, Novispathodinae, Paragondolellinae and Pseudofurnishiinae. The family Gladigondolellidae is monotypic, consisting of the subfamily Gladigondolellinae. The genus Neostrachanognathus is not assigned to any family or subfamily as its origin is unclear. Conodont provincialism was low in the early Anisian, but from the late Anisian faunistic differences started to increase and became stronger during the early Ladinian, reaching a peak around the mid‐Ladinian. Provincialism remained strong until the earliest Carnian and changed to an all‐Triassic low in the early Tuvalian. The provincialism between North America and Tethys rebounded on the specific level during the late Tuvalian. Diversities on generic and specific levels have been established, and two major conodont diversity cycles are recognized: the first ranges from the Bithynian (early Anisian) to the Julian (late early Carnian), and the second is restricted to the Tuvalian (late Carnian).